دور الوعي البيئي في إدارة النفايات البلدية الصلبة دراسة ميدانية في محافظة اللاذقية - شاهين, هيثم; طيوب, محمود; أحمد, صفاء حكمت (Latakia University Journal - Economic and Legal Sciences Series, 2015)
تتفاقم مشكلة النفايات يوماً بعد آخر مما يسبب عبأً ثقيلاً على كاهل البلديات التي تقف عاجزة عن معالجتها في الكثير من الحالات. فالإنسان هو المسؤول الأول عن تشكل النفايات، وأي برنامج لإدارة النفايات البلدية الصلبة يجب أن يأخذ بعين الاعتبار دور الوعي البيئي لدى المواطنين من ناحيتين: الأولى دوره في التقليل من كمية النفايات المتولدة من خلال تحسين سلوكياته وعاداته الغذائية, والثانية من خلال العمل على تعزيز دوره في المساهمة مع البلدية في علميات الفرز والتدوير واستعداده لشراء السلع المدورة, مما يسهم في تخفيف التكاليف، وبالتالي تحسين مستوى الإدارة والاستفادة من النفايات والوصول إلى بيئة أفضل. يهدف البحثالتعرف على درجة تواجد الوعي البيئي حول إدارة النفايات الصلبة في محافظة اللاذقية من وجهة نظر أفراد عينة البحث,والتعرف إلى الفروق فيآرائهم تبعاً للمتغيرات المدروسة (الجنس، المستوى التعليمي، مكان الإقامة). طبّق البحث على عينة من سكان محافظة اللاذقية، والبالغ عددها (280) فرداً.استخدمالباحث الاستبانة، التي تم الاعتماد عليهافيالتوصلإلىنتائجالبحث المدونة ادناه،وتم التأكد من ثبات الاستبانة بطريقتين الأولى طريقة التجزئة النصفية،وبلغ معامل الثبات (0.829)، والثانية طريقة معادلة كرونباخ ألفا وبلغمعامل الثبات بلغ (0.793)، وهي معاملات ثبات مقبولة إحصائياً.وتوصلت الدراسة إلى نتائج أهمها:وجود وعي بيئي حول خطورة النفايات الصلبة على حياتنا واعتبارها مصدر للتلوث والأمراض, ووجود استعداد اجتماعي للمساهمة في إدارة النفايات الصلبة كالفرز المنزلي أو العمل في جمعيات بيئية.كما أن الوعي البيئي ينتشر في المحافظة ككل ولكن يلاحظ الاهتمام بالبيئة في المدينة أكثر من الريف. كما تبين أن الوعي البيئي يرتبط بالمستوى الثقافي, حيث لوحظ ارتفاع مستوى الوعي لدى الفئات المثقفة أكثر من غيرهم. وقد لوحظ تساوي الوعي البيئي بين الذكور والاناث. وقد خلص البحث إلى مقترحات أهمها: الاهتمام بنشر الوعي البيئي بشكل أكبر لدى الفئات المجتمعية غير المثقفة، بالإضافة إلى نشر ثقافة العمل التطوعي في مجال البيئة. The problem of waste is getting worse day by day, which may represent a heavy burden on municipalities, that they are unable to process it in most situations. Man is primarily responsible for the waste form, and any scheme for management municipal solid waste most take into account the role environmental awareness among the citizens of north sides: the first is to reduce the amount of waste produced through improving people's behavior's and their dietony habits. The second by working to strengthen its role in contributing to with the municipality in sorting and recycling and willingness to buy recycled good, which contributes to ease costs, and thus improve the management. The aim of this research to identify the degree of presence environmental awareness about the management of solid waste in the province of Lattakia from the point of view of the mushers of research sample. And to identify the differences in their views depending on the variables studied (sex gender, educational level, place of residence). Research Applied on a sample of the population of the province of Lattakia that number had reached 280 people. The researcher used the questionnaire, which was relied upon in reaching the results of the study, was to ensure the stability of the resolution in two ways: first way retail midterm has reached stability coefficient (0.829), and the second method equation Cronbach alpha was the reliability coefficient was (0.793), a transaction firming acceptable statistically. The study reached the following conclusions: the presence of environmental awareness about the seriousness of solid waste on our lives and consider it the source of contamination and disease. And the existence of a social willingness to contribute to the management of solid waste as sort of domestic or work in environmental associations. The environmental awareness is spreading in the province as a whole, but noted concern for the environment in the city, most of the countryside. As environmental awareness associated cultural level where it was noted the high level of awareness among the educated classes more than illiterate. It has been observed is that to the environmental awareness is equally between males and females. The research found the most important proposals : attention to publish more environmental awareness among community groups is an educated in addition to spreading the culture of voluntary work in the field of environment an educated.